Bioacoustic analysis in Scinax hayii (Barbour, 1909) (Anura, Hylidae) at its type locality in Petrópolis, Rio de Janeiro, Brazil - Santos, Lucas Rodrigo Dos; Martins, Itamar Alves (Magnolia Press, 2017)
Scinax hayii was described in 1909 from the municipality of Petrópolis, State of Rio de Janeiro, Brazil. Morphological variation and advertisement calls have been previously reported for other populations across the species distribution (Lutz 1973; Heyer et al. 1990; Cardoso & Andrade 1991; Pombal et al. 1995; Magrini et al. 2011; Abrunhosa et al. 2014). However, no information on calls are available from specimens recorded at the type locality, preventing the correct characterization of the species (Magrini et al. 2011). Here we describe the advertisement call and a second call type of S. hayii from Petrópolis, as a contribution towards a better understanding of the taxonomy of this species.
Keywords: Amphibia, Anura, Hylidae